Optimization of control of crops’ weed-infested of soybean farming with different systems in Right Bank Forest-Steppe zone of Ukraine - Танчик, С. П.; Мигловець, О. П. (Scientific Progress & Innovations, 2015)
The main results of research on the impact of soil and insurance herbicides on weediness of crops for cultivation of soybean under different farming systems (industrial and no-till) are presented. It was established that the greatest efficiency of soil and insurance herbicides and the lowest level of contamination was marked in the application of tank mixes before sprouting and during the growing season and crops, which influences the crop soybeans. Pre-sowing weed synusia is effectively destroyed by total herbicides continuous action system of no-till.